2019
DOI: 10.1038/s41598-019-55419-w
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Tau Oligomers Modulated by Novel Curcumin Derivatives

Abstract: The pathological aggregation and accumulation of tau, a microtubule-associated protein, is a common feature amongst more than 18 different neurodegenerative diseases that are collectively known as tauopathies. Recently, it has been demonstrated that the soluble and hydrophobic tau oligomers are highly toxic in vitro due to their capacity towards seeding tau misfolding, thereby propagating the tau pathology seen across different neurodegenerative diseases. Modulating the aggregation state of tau oligomers throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 86 publications
2
84
0
Order By: Relevance
“…We recently showed that synthetic curcumin derivatives interact with TauO, resulting in the formation of larger tau aggregates with decreased associated neurotoxicity ( 48 ). These novel curcumin derivatives are characterized by the removal of the β-diketo moiety that exhibits keto-enol tautomerism and is thought to be responsible for the low curcumin brain bioavailability ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that synthetic curcumin derivatives interact with TauO, resulting in the formation of larger tau aggregates with decreased associated neurotoxicity ( 48 ). These novel curcumin derivatives are characterized by the removal of the β-diketo moiety that exhibits keto-enol tautomerism and is thought to be responsible for the low curcumin brain bioavailability ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that newly synthesized curcumin derivatives/analogs, with low toxicity profile, can interact with preformed toxic tau oligomers by reshaping their conformation, resulting in the formation of larger tau structures with decreased toxicity in human neuroblastoma cells and primary cortical neurons ( 48 ). In the current study, we expanded this investigation to disease-relevant tau oligomers isolated from AD, DLB, and PSP brain tissues.…”
mentioning
confidence: 99%
“…This issue needs to be clarified in future research. Considering the pleotropic effect of curcumin on neurodegenerative diseases, cancers and immune disorders, curcumin is a promising substance for treating disease today without causal treatment [1,2,10,[51][52][53][54][55][56][57]. In addition, it is a safe, inexpensive substance, easily accessible and penetrates the blood-brain barrier and neuronal membranes, which is its great advantage [1][2][3]7].…”
Section: Resultsmentioning
confidence: 99%
“…The research aimed at the discovery of HSP60 inhibitors may be attractive and can lead to finding anticancer agents' adjuvants in combination with chemotherapy, thus to reduce both the adverse effects and drug resistance as well as increase the effective targeting of cancerous cells. In this field, curcumin, which is a polyphenolic compound found in turmeric, with anti-inflammatory, antioxidant, and anti-aggregation properties, has been extensively studied for its neuroprotective effects [17][18][19]. Curcumin has numerous molecular targets, and its anti-tumoral mechanisms of action, including cellular proliferation, apoptosis, autophagy, angiogenesis, immune-modulation, invasion, and metastasis, have been widely studied [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, little is still known about its role in ameliorating the stress in cancer and its impact on the components of CS, which are the main regulators of cellular stress. On the other hand, the therapeutic benefits of curcumin, which is known to interfere with protein aggregation in neurodegenerative diseases, appear to be multifactorial and associated with the regulation of transcription factors functioning, or linked with the activity of different proteins [17][18][19][20]. Curcumin and several natural derived-products have been shown to regulate many members of HSPs.…”
Section: Introductionmentioning
confidence: 99%